Do compression sleeves worn during exercise affect muscle recovery? - Pereira, M. C.; Bottaro, M.; Brown, L. E.; Rocha-Junior, V. A.; Martorelli, S. S.; Nobrega, O. T.; Souza, V. C.; Pinto, R. S; Carmo, J. (Isokinetics and Exercise Science, 2014)
BACKGROUND: Athletes often wear compression sleeves, yet studies on their effects are lacking. OBJECTIVE: The aim of this study was to determine the effect of compression sleeves worn during exercise on muscle recovery following exercise. METHODS: Twenty-two resistance trained men were randomly assigned to either a compression sleeve (GCS, n=11) or placebo sleeve (GPS, n=11) group. They performed 4 sets of 10 isokinetic eccentric/concentric elbow flexion repetitions. Isometric peak torque, muscle activation, echo intensity and perceived muscle soreness were measured at baseline, immediately after and 24, 48, 72 and 96~hours post exercise. Blood CK samples were obtained at baseline, 48 and 96 hours post exercise. RESULTS: There were no significant interactions or main effects for group regarding any of the variables (P > 0.05). There were main effects for time for all variables except muscle activation. Isometric peak torque immediately after and 24, 48, 72 and 96 hours were all significantly less than baseline. Echo intensity immediately after was significantly greater than baseline. Perceived muscle soreness at 48 h was greater than baseline. CK levels at 48 and 96 hours were greater than baseline. CONCLUSIONS: The use of compression sleeves is not recommended for the alleged enhancement of muscle recovery following upper body high-intensity exercise in young resistance-trained men. ABSTRACT FROM AUTHOR